Beyond Value in Moral Phenomenology: The Role of Epistemic and Control Experiences - Cornwell, James F. M.; Higgins, E. Tory (Frontiers in Psychology, 2019)
Many researchers in moral psychology approach the topic of moral judgment in terms of value—assessing outcomes of behaviors as either harmful or helpful which makes the behaviors wrong or right, respectively. However, recent advances in motivation science suggest that other motives may be at work as well—namely truth (wanting to establish what is real) and control (wanting to manage what happens). In this review, we argue that the epistemic experiences of observers of (im)moral behaviors, and the perceived epistemic experiences of those observed, serve as a groundwork for understanding how truth and control motives are implicated in the moral judgment process. We also discuss relations between this framework and recent work from across the field of moral psychology, as well as implications for future research.